Influence of the calcination temperature on the catalytic properties of Os/bentonite for glycerol hydrogenolysis - Hamzah, Noraini; Samad, Wan Zurina; Yarmo, Mohd Ambar (Trans Tech Publications Ltd., 2017)
Selective catalytic hydrogenolysis of glycerol on Os/bentonite catalyst represents a low cost and green route for 1,2-propanediol which is major community chemical used in the production of antifreeze functional fluids, paints and humectants. The experimental results combined with the characterization studies using TPR, FESEM-EDX and XPS techniques revealed that the optimum calcination temperature was 300 °C with glycerol conversion obtained was 80.7%. This might be due to the presence of Os metal species as an active site with binding energy(BE) of Os 4f at 51.2 eV in XPS analysis. TPR profile also shows two obvious peak at reduction temperature of 95 °C and 140 °C represent for Os3+ and Os4+ species respectively. The presence of Os3+ and Os4+ species were also confirmed by XPS analysis.